Semantic Analysis of Toshihiko Izutsu's Perspective on the Meaning of Amal (أمل) in the Qur'an - Muna, Navisa Izzatil; Nugroho, Kharis; Mustofa, Asrizal (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyze the meaning of the word amal (أمل) in the Qur'an using the semantic approach of Toshihiko Izutsu. This approach emphasizes understanding the basic, relational, and historical meanings of a term in the linguistic and theological context of the Qur'an. This study uses a qualitative descriptive method with syntagmatic and paradigmatic analysis of Qur'anic verses that contain the word amal. The results of the analysis show that the meaning of amal in the Qur'an includes two main poles: as an empty hope that is negligent (QS. Al-Hijr: 3) and as a positive, directed, and related hope to righteous deeds and awareness of the hereafter (QS. Al-Kahfi: 46). Paradigmatically speaking, amal has synonymous relationships with raja', ṭama', and tamanni, as well as antonyms with ya'isa and qanata. Historically, the meaning of amal has evolved from a worldly expectation in the pre-Qur'anic period to a religious and transcendental meaning in the Qur'anic and post-Qur'anic periods. In the context of the Qur’anic weltanschauung, amal reflects a view of life that emphasizes optimism, spiritual responsibility, and awareness of divine values. These findings confirm that the language in the Qur'an is not just a means of communication, but also a medium for the formation of a distinctive and dynamic worldview.